SWOT Analysis as a Competitive Strategy at Primkop Kartika Ardagusema Cimahi City, West Java, Indonesia - Wiara Sanchia Grafita Ryana Devi; Desty Rara Pringgandinie; Henly Yulina; Deni Hadiansah (Publisher Cv. Inara, 2022)
In the current era of globalization, companies must be able to design a competitive strategy so as not to compete with other companies, a competitive strategy is one way for companies to find out their competitiveness in every strength that exists in a company. Every company must have a competitive advantage that other companies do not have. To design a competitive strategy the company can use a SWOT analysis. The effective use of SWOT analysis can play an important role in determining competitive strategies, in order to know the strengths, weaknesses, opportunities and threats faced by the company in maintaining the company's survival. The purpose of this study was to determine whether SWOT analysis is an appropriate strategy in increasing company production and how competitive strategies are carried out by a company to be able to compete in the era of globalization. This research data collection uses secondary data in obtaining data, archives, and documents. From the research that has been done, it is found that the results of the data that have been analyzed using a SWOT matrix from several internal factors, in the form of strengths and weaknesses, as well as external factors in the form of opportunities and threats to determine the competitive strategy for the Kartika Ardagusema Cooperative, is to carry out a diversification strategy (product, market).